Knowledge and practice of primary care nurses about gender and care for LGBTQIA+ people - Elisama Ferreira Paiva; Rodrigo Jácob Moreira de Freitas; Marcelino Maia Bessa; Janieiry Lima de Araújo; Sâmara Fontes Fernandes; Palmyra Sayonara de Góis (Universidade Federal do Ceará, 2023)
Objective: to understand the knowledge and practice of Primary Health Care nurses about gender and assistance to LGBTQIA+ people. Methods: qualitative study, conducted with nine nurses from Primary Health Care. Data were collected through semi-structured interviews and submitted to Thematic Content Analysis. Results: three categories emerged: knowledge about gender and the LGBTQIA+ population; perception of the National LGBT Comprehensive Health Policy; and demand for services and nursing care for the LGBTQIA+ public. Conclusion: it was evidenced deficient knowledge about gender and health of the LGBTQIA+ population. There is a lack of preparation of the professionals who assist these users, which causes barriers to access to care and services, due to the lack of knowledge about the existence of the national policy of integral health of this population. Nurses focus on punctual and biologist actions. Contributions to practice: the findings contribute to subsidize the thinking/doing of nursing regarding vulnerable populations, who need an equitable, integral, and humanized look. It is necessary to strengthen discussions in health training and continuing education to expand knowledge about gender, the access of the LGBTQIA+ population to services and the consolidation of the actions of the national health policy aimed at this population group.